The Relationship Between Family Support And Self-Management In Post-Stroke Patients - Isna Amalia Mutiara Dewi; Anggi Pratiwi; Tyra Septi Diana (Universitas Pahlawan Tuanku Tambusai, 2026)
Stroke is a leading cause of disability and the second leading cause of death worldwide, significantly affecting patients' physical, psychological, and social aspects of life. This condition requires post-stroke patients to have adequate self-management abilities to support optimal recovery. Family support plays an important role as a primary support system in enhancing patients' ability to manage their illness. This study aimed to determine the relationship between family support and self-management among post-stroke patients. This study employed a quantitative design with a correlational analytical approach and a cross-sectional method. The sample consisted of 72 post-stroke patients attending outpatient care at the Neurology Clinic, selected using purposive sampling. Research instruments included a family support questionnaire and the Southampton Stroke Self-Management Questionnaire (SSSMQ). The results showed a significant positive relationship between family support and self management among post-stroke patients (r = 0.609; p < 0.05). Adequate family support contributes to improved self-management abilities in post-stroke patients.